The warning bell of Dolutegravir resistance: rethinking HIV service models in Africa - Ciccacci, Fausto; Welu, Benjamin; Uamusse, Elton; Guidotti, Giovanni; Vaz, Yolanda; Capparucci, Stefano; Iasilli, Gianna; Thembo, Dyna; Scarcella, Paola (Frontiers in Public Health, 2025)
The emergence of resistance to Dolutegravir (DTG)—the cornerstone of first-line antiretroviral therapy—marks a critical turning point in the fight against HIV in Africa. Once considered unlikely due to DTG’s high genetic barrier, resistance is now increasingly reported, raising urgent questions about current HIV service models. This Perspective argues that the spread of resistance must be seen not only as a clinical threat but as a warning signal for the broader health system, especially in the wake of post-COVID transformations that have accelerated decentralization, task-shifting, and self-managed care. While such innovations offer benefits, they also risk eroding human connection and clinical oversight, which are essential in managing a complex condition like HIV. Drawing on experience from the DREAM program and other field evidence, we identify four strategic priorities for a renewed response: scaling up differentiated service delivery (DSD), expanding access to resistance testing, strengthening community-based support, and ensuring equitable access to advanced treatment options. These pillars aim to safeguard past achievements while adapting to emerging challenges. We call for urgent, equity-driven action to prevent further spread of resistance and to build resilient, person-centered systems capable of delivering sustainable HIV care in Africa and beyond.